The Kidney-Vascular-Bone Axis in the Chronic Kidney Disease-Mineral Bone Disorder. Issue 3 (March 2016) - Seifert, Michael E.; Hruska, Keith A.
Abstract : The last 25 years have been characterized by dramatic improvements in short-term patient and allograft survival after kidney transplantation. Long-term patient and allograft survival remains limited by cardiovascular disease and chronic allograft injury, among other factors. Cardiovascular disease remains a significant contributor to mortality in native chronic kidney disease as well as cardiovascular mortality in chronic kidney disease more than doubles that of the general population. The chronic kidney disease (CKD)-mineral bone disorder (MBD) is a syndrome recently coined to embody the biochemical, skeletal, and cardiovascular pathophysiology that results from disrupting the complex systems biology between the kidney, skeleton, and cardiovascular system in native and transplant kidney disease. The CKD-MBD is a unique kidney disease-specific syndrome containing novel cardiovascular risk factors, with an impact reaching far beyond traditional notions of renal osteodystrophy and hyperparathyroidism. This overview reviews current knowledge of the pathophysiology of the CKD-MBD, including emerging concepts surrounding the importance of circulating pathogenic factors released from the injured kidney that directly cause cardiovascular disease in native and transplant chronic kidney disease, with potential application to mechanisms of chronic allograft injury and vasculopathy. Abstract : In a very elegant review, the authors explain the implications and new risk factors of a novel entity, chronic kidney disease-mineral bone disorder, related to the burden of cardiovascular diseases in both native chronic kidney disease and kidney transplant settings.